Instilling Entrepreneurial Characteristics Through Islamic Religious Education - Jayanti, Suwarni; Aripuddin, Aripuddin; Nurwahida, Andi; Susono, Juhasdi; Azis, Abd (International Journal on Advanced Science, Education, and Religion, 2025)
Islamic Religious Education (PAI) not only serves as a vehicle for instilling spiritual values, but also has a strategic role in shaping the character of students to be independent, creative, and responsible—characteristics that align with the spirit of entrepreneurship. This study aims to analyze the role of PAI in instilling entrepreneurial characteristics through an Islamic values ​​approach. The research method is a qualitative type using a literature review (library research). The results of the study indicate that there are four main characteristics that are relevant and contextual to PAI values, namely: (1)Have the courage to face challenges (Risks),(2)Able to create new and innovative ideas,(3)Consistent in Carrying Out Responsibilities and Diligent Towards Goals, and(4)Skilled in Utilizing Time and Managing Potential Effectively and EfficientlyThe implications of these findings indicate that instilling entrepreneurial values ​​in Islamic Religious Education (PAI) learning not only enriches character education but also strengthens students' spiritual and ethical dimensions in facing the challenges of life and the business world.